Investigation of the strain-rate-dependent mechanical behavior of a photopolymer matrix composite with fumed nano-silica filler - Asif, Muhammad; Ramezani, Maziar; Khan, Kamran Ahmed; Khan, Muhammad Ali; Aw, Kean Chin (Wiley, 2019)
With the evolution of additive manufacturing, there is an increasing demand to produce high strength and stiffness polymers. Photopolymers are very commonly used in stereolithography and fused deposition modeling processes, but their application is limited due to their low strength and stiffness values. Nano‐sized fibers or particles are generally embedded in the polymer matrix to enhance their properties. In this study, we have studied the effect of fumed nano‐sized silica filler on the elastic and viscoelastic properties of the photopolymer. The uniaxial testing coupons with different concentrations of silica filler have been fabricated via casting. We observed improvement in mechanical properties by the addition of the nano‐sized filler. As polymers exhibit time‐dependent mechanical response, we have conducted tensile tests at different strain rates as it is one of the most common modes of deformation, and is commonly used to characterize the parameters of the rate‐dependent material. We noticed significant dependence of the mechanical properties on the strain rate. quasi‐linear viscoelastic (QLV) model, which combines hyperelastic and viscoelastic phenomena, has been employed to capture the response of the material at different strain rates. We found out that the QLV model with Yeoh strain energy density function adequately describes the rate‐dependent behavior of the material and has reasonable agreement with the experimental results.